A new species of Gaylordia Paula Couto (Mammalia, Metatheria) from Itaboraí, Brazil - Oliveira, Édison Vicente (2015)
We describe a new metatherian of the genus Gaylordia Paula Couto, from the early Eocene Itaboraí Basin, Brazil. This new species (estimated body mass ~60-90.9 g) is based on lower and upper dentition elements and is characterized by a more plesiomorphic dental morphology with respect to G. macrocynodonta Paula Couto (with a larger body mass, estimated in ~74-103 g for large individuals or males). The species G. doelloi Marshall, represented by small individuals or females, is regarded a junior synonym of G. macrocynodonta. A phylogenetic analysis as well as details of the occlusal surface of its upper and lower molars suggests that Gaylordia is closely related to the Pucadelphyidae, a non-marsupial “ameridelphian” group previously recorded at the early Paleocene locality of Tiupampa, Bolivia.